Leibniz on Existence - Ottaviani, Osvaldo (Milano University Press, 2025)
Leibniz on Existence offers a systematic reconstruction of Leibniz’s evolving conception of existence, combining historical and analytical approaches. It argues that Leibniz conceives existence on three interconnected levels—phenomenological (real vs. imaginary), ontological (concrete vs. abstract), and modal (actual vs. possible)—and that the tensions among these levels are structural to his metaphysics. Tracing his thought from its nominalist beginnings to the mature theory of possible worlds, the book shows how Leibniz’s reflections on existence illuminate the interplay between rational theology, metaphysics, and the relation between the possible and the actual.